INCIDENCE AND MORTALITY FROM BREAST CANCER IN THE MALE AND FEMALE POPULATION OF CENTRAL SERBIA IN THE PERIOD 2009-2020 - Nikolic, Aleksandra; Micanovic, Danilo; Mitrasinovic, Petar; Murtezani, Zafir; Banasevic, Marijana; Sipetic Grujicic, Sandra (HEALTH CARE, 2023)
Introduction/Aim: In 2020, globally, breast cancer was the leading cause of morbidity when both sexes are considered together, followed by prostate cancer and lung cancer. However, breast cancer is very rare in men. In this descriptive study, incidence and mortality from breast cancer was analyzed in the population of men and women in Central Serbia for the period from 2009 to 2020. Methods: Data on patients and deaths from breast cancer, as well as the number of inhabitants, by gender and age, were taken from published and unpublished material of the Institute for Public Health of Serbia "Dr. Milan Jovanović Batut". General, specific and standardized incidence and mortality rates were used in the analysis. Joinpoint regression analysis was used to analyze trends in morbidity and mortality.Results: In the period 2009-2020, the average standardized incidence rate (per 100,000) of breast cancer for men was 1.3, and for women 65.3, and the mortality rate (per 100,000) for women was 19.8, and for men 0.4. During the observed period, the standardized incidence rate for men increased by 1.9% per year and the mortality rate by 2.4%, but without significance. In women, the standardized incidence rate increased significantly by 3.5% per year in the period 2013-2020, and the standardized mortality rate significantly decreased by -0.5% per year in the period 2009-2020. In both sexes, mortality and incidence rates increased with age, except that in women the incidence rate for the age of 70 and over was lower compared to the incidence rate for the age of 60-69.Conclusion: It is necessary to further improve the implementation of organized screening for breast cancer in the territory of Central Serbia, as well as to work on the reduction/elimination of risk factors and raise the awareness of men about the possibility that they can be affected by breast cancer.
Keywords: descriptive study, breast cancer, incidence, mortality, joinpoint regression analysis